Morphological and histochemical changes in the brain stem in case of experimental hemispheric intracerebral hemorrhage - S. I. Tertishniy (Zaporožskij Medicinskij Žurnal)
Aim. Investigation of the extent of morphological changes and activity of biogenic amines (according to the intensity of luminescence) in the neurons of the brain stem in intracerebral hemorrhage (ICH).